The real-world clinical effectiveness of durvalumab in advanced biliary tract cancer: a mimic comparative analysis through survival data reconstruction - Ji, Hong-xiang; Si, Ma-Hui; Sun, Zhe; Yang, Ning; Chen, Zhan (Frontiers in Immunology, 2025)
BackgroundThe TOPAZ-1 study results represented significant advancement in the treatment of advanced biliary tract cancer (BTC) by combining durvalumab with gemcitabine–cisplatin (DGC). However, the highly selected patient population may not reflect the real-world scenarios. To gain deeper insights into this combination regimen, we conducted an evidence collection and a mimic survival comparative analysis.MethodsRecords were identified through a formal search of PubMed and Web of Science. Six retrospective cohort studies with real-world evidence were definitively included. The individual patient data for OS and PFS were reconstructed and analyzed. The outcomes different from TOPAZ-1 were summarized and compared.ResultsWhether Asia or non-Asia group, the mOS was similar to the TOPAZ-1 (Asian group: 12.57 months vs. TOPAZ-1, HR = 0.91, 95% CI: 0.69-1.21, log rank P = 0.53; non-Asian group: 13.61 months vs. TOPAZ-1, HR = 1.10, 95% CI: 0.91-1.31, log rank P = 0.323). The mPFS for the Asian group did not show significant differences compared with TOPAZ-1 (5.63 months vs. TOPAZ-1, HR = 1.09, 95% CI: 0.88-1.35, log rank P = 0.422), whereas for the non-Asian group differences exist (6.58 months vs. TOPAZ-1, HR = 0.80, 95% CI: 0.70-0.92, log rank P = 0.002), but potentially influenced by patient ethnicity. The disease control rate in the real world was not so favorable as that in TOPAZ-1. The most common adverse events (AEs) in real-world scenarios were fatigue (26.01%), leukopenia (24.64%), anemia (24.30%), and thrombocytopenia (21.14%). The incidence of immune-related AEs of grades 3–4 was slightly higher in the real world compared with TOPAZ-1 (4.0% vs. 2.4%). Factors such as ECOG-PS, age, alternative doses of durvalumab, neutrophil-to-lymphocyte ratio (NLR), baseline CEA levels, baseline CA19–9 levels, and metastatic disease could be prognostic factors under DGC regimen, with NLR showing a potential as a predictive marker for survival benefit.ConclusionsThe efficacy and safety of the DGC regimen for patients with advanced BTC are confirmed through a comparative analysis and aggregation of real-world evidence in this study. Further real-world investigations are still warranted to determine if the DGC regimen has a broader therapeutic indication and to identify predictive markers for survival benefit. Efforts are required to improve the cost-effectiveness of the DGC regimen to facilitate its wider and standardized use.